A unique cytotoxic CD4+ T cell‐signature defines critical COVID‐19 - Sarah Baird; Caroline L Ashley; Felix Marsh‐Wakefield; Sibel Alca; Thomas M Ashhurst; Angela L Ferguson; Hannah Lukeman; Claudio Counoupas; Jeffrey J Post; Pamela Konecny; Adam Bartlett; Marianne Martinello; et al. (Clinical & Translational Immunology, 2023)
Abstract Objectives SARS‐CoV‐2 infection causes a spectrum of clinical disease presentation, ranging from asymptomatic to fatal. While neutralising antibody (NAb) responses correlate with protection against symptomatic and severe infection, the contribution of the T‐cell response to disease resolution or progression is still unclear. As newly emerging variants of concern have the capacity to partially escape NAb responses, defining the contribution of individual T‐cell subsets to disease outcome is imperative to inform the development of next‐generation COVID‐19 vaccines. Methods Immunophenotyping of T‐cell responses in unvaccinated individuals was performed, representing the full spectrum of COVID‐19 clinical presentation. Computational and manual analyses were used to identify T‐cell populations associated with distinct disease states. Results Critical SARS‐CoV‐2 infection was characterised by an increase in activated and cytotoxic CD4+ lymphocytes (CTL). These CD4+ CTLs were largely absent in asymptomatic to severe disease states. In contrast, non‐critical COVID‐19 was associated with high frequencies of naïve T cells and lack of activation marker expression. Conclusion Highly activated and cytotoxic CD4+ T‐cell responses may contribute to cell‐mediated host tissue damage and progression of COVID‐19. Induction of these potentially detrimental T‐cell responses should be considered when developing and implementing effective COVID‐19 control strategies.